Schooling and Labor Market Consequences of School Construction in Indonesia: Comment - David Roodman (Institute for Replication (I4R), 2023)
Duflo (2001) exploits a 1970s schooling expansion in Indonesia to estimate the returns to schooling. Under the study's difference-in-differences (DID) design, two patterns in the data-shallower pay scales for younger workers and negative selection in treatment-can violate the parallel trends assumption and upward-bias results. In response, I follow up later, test for trend breaks timed to the intervention, and perform changes-in-changes (CIC). I also correct data errors, cluster variance estimates, incorporate survey weights to correct for en-dogenous sampling, and test for (and detect) instrument weakness. Weak identification-robust inference yields imprecise, positive estimates. CIC estimates tilt slightly negative.
Keywords: I2; J31; O15; 330; education; wages; reanalysis